Functional Heterogeneity of Umbilical Cord Blood Monocyte-Derived Dendritic Cells - Schweiger, Petra; Hamann, Livia; Strobel, Julian; Weisbach, Volker; Wandersee, Alexandra; Christ, Julia; Kehl, Sven; Weidenthaler, Filip; Antoniadis, Sophia; Hackstein, Holger; Cunningham, Sarah (Journal of Immunology, 2024)
Human umbilical cord blood (UCB) represents a unique resource for hematopoietic stem cell transplantation for children and patients lacking suitable donors. UCB harbors a diverse set of leukocytes such as professional APCs, including monocytes, that could act as a novel source for cellular therapies. However, the immunological properties of UCB monocytes and monocyte-derived dendritic cells (MoDCs) are not fully characterized. In this study, we characterized the phenotype and functions of UCB-MoDCs to gauge their potential for future applications. UCB exhibited higher frequencies of platelets and lymphocytes as well as lower frequencies of neutrophils in comparison with adult whole blood. Leukocyte subset evaluation revealed significantly lower frequencies of granulocytes, NK cells, and CD14+CD16− monocytes. Surface marker evaluation revealed significantly lower rates of costimulatory molecules CD80 and CD83 while chemokine receptors CCR7 and CXCR4, as well as markers for Ag presentation, were similarly expressed. UCB-MoDCs were sensitive to TLR1–9 stimulation and presented quantitative differences in the release of proinflammatory cytokines. UCB-MoDCs presented functional CCR7-, CXCR4-, and CCR5-associated migratory behavior as well as adequate receptor- and micropinocytosis-mediated Ag uptake. When cocultured with allogeneic T lymphocytes, UCB-MoDCs induced weak CD4+ T lymphocyte proliferation, CD71 expression, and release of IFN-γ and IL-2. Taken together, UCB-MoDCs present potentially advantageous properties for future medical applications.<br

Smart sensing in pregnancy: a survey-based evaluation of readiness to use wearable sensory applications in prenatal care - Weidenthaler, Filip; Danzberger, Nina; Pontones, Constanza; Titzmann, Adriana; Hein, Alexander; Beckmann, Matthias; Fasching, Peter; Huebner, H. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04